Determination of hydroxy-s-triazines in water using HPLC or GC-MS - Färber, Harald; Nick, Klaus; Schöler, Heinz Friedrich (Fresenius' journal of analytical chemistry, 1994)
Two methods are described for the routine determination of triazine degradation products in water. After solid phase extraction by means of RP-C18 cartridges, the separation and detection were carried out using either HPLC (for hydroxy-atrazine [OHA], hydroxy-simazine [OHS], hydroxy-propazine [OHP], hydroxy-terbutylazine [OHT] and hydroxy-desethylatrazine [OHDEA]) or GC-MS (only for OHA, OHS, OHP and OHT after methylation with diazomethane). The HPLC set-up is described for detecting the hydroxy-triazines, including hydroxy-desisopropylatrazine (OHDIA), hydroxy-desethyldesisopropylatrazine (OHDEDIA) and cyanuric acid (CA). The average recoveries at concentration levels between 50 ng/L and 1 μg/L ranged from 35% to 43% for GC-MS (n=5) and from 53% to 75% for HPLC (n=5) with the exception of hydroxy-desethylatrazine which has been recovered with only 21%. Hydroxy-desisopropylatrazine, hydroxy-desethyldesisopropylatrazine and cyanuric acid could not be enriched on RPC18. The determination limit of the investigated compounds has to be set between 90 and 100 ng/L for both methods for OHS, OHA, OHP and OHT.
Gesehen am 08.02.2023